Challenges and policy opportunities in nursing in Saudi Arabia - Mohammed Alluhidan; Nabiha Tashkandi; Fahad Alblowi; Tagwa Omer; Taghred Alghaith; Hussah Alghodaier; Nahar Alazemi; Kate Tulenko; Christopher H. Herbst; Mariam M. Hamza; Mohammed G. Alghamdi (BMC, 2020)
Abstract Background The Kingdom of Saudi Arabia's (KSA) health sector is undergoing rapid reform in line with the National Transformation Program, as part of Saudi's vision for the future, Vision 2030. From a nursing human resources for health (HRH) perspective, there are challenges of low nursing school capacity, high employment of expatriates, labor market fragmentation, shortage of nurses in rural areas, uneven quality, and gender challenges. Case presentation This case study summarizes Saudi Ministry of Health (MOH) and Saudi Health Council's (SHCs) evaluation of the current challenges facing the nursing profession in the KSA. We propose policy interventions to support the transformation of nursing into a profession that contributes to efficient, high-quality healthcare for every Saudi citizen. Key to the success of modernizing the Saudi workforce will be an improved pipeline of nurses that leads from middle and high school to nursing school; followed by a diverse career path that includes postgraduate education. To retain nurses in the profession, there are opportunities to make nursing practice more attractive and family friendly. Interventions include reducing shift length, redesigning the nursing team to add more allied health workers, and introducing locum tenens staffing to balance work-load. There are opportunities to modernize existing nurse postgraduate education, open new postgraduate programs in nursing, and create new positions and career paths for nurses such as telenursing, informatics, and quality. Rural pipelines should be created, with incentives and increased compensation packages for underserved areas. Conclusions Critical to these proposed reforms is the collaboration of the MOH with partners across the healthcare system, particularly the private sector. Human resources planning should be sector-wide and nursing leadership should be strengthened at all levels.